The Influence of Different Forms of Lexical Annotation on the Incidental Vocabulary Learning of Chinese Students based on Multimedia Technology. Issue 2 (August 2021) - Jiang, Shifang; Jin, Di
Abstract: The development of multimedia technology makes English learning more and more simple. This paper mainly studies the influence of four different annotation forms, namely Chinese, English, Chinese + pictures and English + pictures. The results showed that the Chinese annotations were more effective than the English annotations in promoting incidental vocabulary learning. The combination of text and picture annotation is more conducive to incidental vocabulary learning than the text-only annotation. Among the four kinds of annotations, the combination of Chinese and pictures is the most effective for incidental vocabulary learning. Those with higher English proficiency are significantly better than those with lower English proficiency in using annotations to learn vocabulary and maintain word memory.